1) Ta có: \(\frac{x-3}{2-x}=\frac{-2}{3}\)
=> (x - 3).3 = -2.(2 - x)
=> 3x - 9 = -4 + 2x
=> 3x - 2x = -4 + 9
=> x = 5
2) Gọi số nguyên cần điền vào chỗ ... là x
Ta có: \(\frac{8}{-5}+\frac{-12}{7}< x< \frac{-7}{2}+\frac{3}{5}\)
=> \(\frac{-56}{35}+\frac{-60}{35}< x< \frac{-35}{10}+\frac{6}{10}\)
=> \(\frac{-116}{35}< x< \frac{-29}{10}\)
=> -4 < x < -2
Mà \(x\in Z\Rightarrow x=-3\)
1)\(\frac{x-3}{2-x}=\frac{-2}{3}\Rightarrow-2\left(2-x\right)=3\left(x-3\right)\)
\(\Rightarrow2x-4=3x-9\)
\(\Rightarrow x=5\)
2)\(-\frac{8}{5}+\frac{-12}{7}< ...< -\frac{7}{2}+\frac{3}{5}\)
\(\Leftrightarrow\frac{-56}{35}+\frac{-60}{35}< ...< \frac{-35}{10}+\frac{6}{10}\)
\(\Leftrightarrow\frac{-116}{35}< ...< \frac{-29}{10}\)
\(\Leftrightarrow\frac{-232}{70}< ...< \frac{-203}{70}\)
tới đây bn tự liệt kê là xong